2017
DOI: 10.3389/fncel.2017.00030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Bipolar Disorder: Progress Made and Future Challenges

Abstract: Bipolar disorder (BD) is a chronic and progressive psychiatric illness characterized by mood oscillations, with episodes of mania and depression. The impact of BD on patients can be devastating, with up to 15% of patients committing suicide. This disorder is associated with psychiatric and medical comorbidities and patients with a high risk of drug abuse, metabolic and endocrine disorders and vascular disease. Current knowledge of the pathophysiology and molecular mechanisms causing BD is still modest. With no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 193 publications
(229 reference statements)
1
54
0
3
Order By: Relevance
“…In the present study, we found that BD patients with CVDs were characterized by glucose dysregulation since young adulthood and tended to have mania as their first episode. These results suggest that BD pathophysiology may be associated with dysfunctional regulation of both mood and glucose across the adulthood span and therefore supporting the “metabolic mood syndrome” hypothesis of BD [30]. Nevertheless, we should also note that the mania as a first episode was found to increase the risk for CVDs 4.69 times in the present analysis.…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, we found that BD patients with CVDs were characterized by glucose dysregulation since young adulthood and tended to have mania as their first episode. These results suggest that BD pathophysiology may be associated with dysfunctional regulation of both mood and glucose across the adulthood span and therefore supporting the “metabolic mood syndrome” hypothesis of BD [30]. Nevertheless, we should also note that the mania as a first episode was found to increase the risk for CVDs 4.69 times in the present analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Current knowledge of BD's neurobiology and pathophysiology is still modest [8] and with no clear biological markers available, early diagnosis is presently a great challenge to clinicians.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…Moreover, BD patients tend to have high rates of divorce, unemployment, drug abuse and crime as consequence of impaired social cognition, and its impact on patients can be devastating, with approximately 23% of patients with BD reported having suicide attempts [6]. Moreover, individuals with BD diagnosis have a high risk of medical comorbidities such as metabolic (diabetes, obesity and metabolic syndrome) and cardiovascular disorders [7].Current knowledge of BD's neurobiology and pathophysiology is still modest [8] and with no clear biological markers available, early diagnosis is presently a great challenge to clinicians.Pharmacological therapy is often the first-line treatment for BD, followed by psychological [9] and psychosocial interventions [10]. For maintenance pharmacological treatment the main goal is to prevent recurrences of mood episodes, using mood stabilizers (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is strictly correlated with several pathways implicated in neuronal function, synaptic plasticity, autophagy, and DNA methylation [22]. These pathways were also proven to be related to BPD [23-25]. FKBP5 genotypes are also associated with alterations in brain function and structure that affect behavior, particularly in brain regions associated with emotional processing, learning, memory, and inhibition (i.e., amygdala and hippocampus) [26, 27].…”
Section: Introductionmentioning
confidence: 99%